Two new species of the genus Oxytate from China (Araneae: Thomisidae) - Liu, Keke; Liu, Jihe; Xu, Xiang (Zootaxa, 2017)
Two new crab spider species from China are diagnosed, described and illustrated: Oxytate bicornis sp. nov. from Jiangxi and Oxytate palmata sp. nov. from Guangxi. The total number of the known species of Oxytate from China rises to 13 with the addition of two new species described in the present paper.